2007
DOI: 10.1063/1.2822458
|View full text |Cite
|
Sign up to set email alerts
|

Semiempirical pressure-volume-temperature equation of state: MgSiO3 perovskite is an example

Abstract: Simple general formula describing the pressure-volume-temperature relationships ͑p-V-T͒ of elastic solids is constructed from theoretical considerations. The semiempirical equation of state ͑EOS͒ was tested to experiments of perovskite 0 -109 GPa and 293-2000 K. The parameters providing the best fit are B 0 = 267.5 GPa, V 0 = 24.284 cm 3 , ␣ 0 = 2.079ϫ 10 −5 K −1 , ‫ץ‬B 0 / ‫ץ‬p = 1.556, and ‫␣ץ‬ 0 / ‫ץ‬p = −1.098ϫ 10 −7 K −1 GPa −1 . The root-mean-square deviations ͑RMSDs͒ of the residuals are 0.043 cm 3 , 0.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…One of the most important issues in condensed matter sciences, particularly, in geology and geophysics, is to accurately predict the structural and physical properties of solids under high pressure and temperature1234567. In general, a solid-state material under high pressure and temperature can exhibit properties quite different from those found at ambient conditions.…”
mentioning
confidence: 99%
“…One of the most important issues in condensed matter sciences, particularly, in geology and geophysics, is to accurately predict the structural and physical properties of solids under high pressure and temperature1234567. In general, a solid-state material under high pressure and temperature can exhibit properties quite different from those found at ambient conditions.…”
mentioning
confidence: 99%
“…(5) can be used for ambient conditions and at higher temperatures 4 because the introduced error is minor. The molar volume of the solid at the temperature of interest is calculated by using the EoS of Garai 4 , which is given as:…”
mentioning
confidence: 99%
“…It is concluded that the presented theoretical approach can successfully applied to calculate the optimum pressure and temperature conditions for vacancy minimization. Garai (2007) …”
mentioning
confidence: 99%
See 2 more Smart Citations